Strategies to manage volatilities in ports - bunkering ports - Tan, Yi Zhen (Nanyang Technological University, 2022)
In the maritime industry, it is common for ports to face volatility. However, not much has been researched to understand the types of volatility present and the strategies that a port can adopt to better deal with such uncertainties. Thus, this paper aims to help port operators identify factors critical to strategizing when tackling port volatility. In this study, multiple criteria were discussed in light of tackling port volatility – bunkering ports. Findings have shown that customers of bunkering ports prioritized bunker supply to be available while bunkering ports are mainly responsible, thus in major control of the safety and efficiency of the bunkering process.